EMPLOYEES WORK LIFE BALANCE, GARMENTS INDUSTRIES, BANGALORE - MANOJ S , MANOJ KUMAR M, MANOJ N M, DR. M. KATHIRAVAN (Journal of Advanced Zoology, 2023)
One of the major drivers of the nation’s economy and exports in India is the textile sector. For Indian labor, it offers a plethora of employment alternatives. After agriculture, the textile sector is considered India’s second-largest employer. As a result, the expansion and general development of this sector directly affects the advancement of the national economy. If an industry’s personnel is dedicated, it may overcome the ongoing worldwide rivalry and attain greater Availability. Industry needs to supply suitable working circumstances, a suitable working conditions, and adequate facilities to guarantee that all employees perform effectively toward organization goals. Inadequate workspaces and working circumstances affect employees’ work-life balance either directly or indirectly in addition to being the cause of job discontent, higher employee turnover, poor performance, and decreased productivity. It’s critical to preserve skilled workers’ industry satisfaction levels and pinpoint areas where worker WLB needs to be improved in order to keep them on staff.The intention of This research aims to evaluate workers’ fulfillment of their working circumstances in the textile industry and assess how it affects their work-life balance. Madhya Pradesh’s textile industry employed factory workers as the study’s population. Those in management and supervision were not included in the research. The goal between the current study was to provide details and recommendations on how to improve the working conditions for textile sector workers To be able to improve work-life harmony.The majority of work-environment related elements had a negative impact on employees’ work-life balance, according to the findings. The findings also highlight how uncomfortable it is for employed people to work in their current environments, which has serious ramifications for families, businesses, and society as large. It is highly advised that companies implement worker-friendly policies in conjunction with more considerate and supporting families To be able to preserve Work-life equilibrium and foster harmony among employees.